DEPRESSIVE STATES AND SUICIDAL BEHAVIORS IN PATIENTS WITH CANCER - Khasanova, K.D.; Gafur-Akhunov, M.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
This article deals with mental disorders in oncology. The characteristic features of depressive states and suicidal behaviors in patients with oncological diseases are analyzed. Based on the analysis, they came to the conclusion that the problem is poorly understood, but it is promising in terms of further, broader study in the field of psychosomatics.